Program of Rehabilitative Exercise and Education to Avert Vascular Events After Non-Disabling Stroke or Transient Ischemic Attack (PREVENT Trial): A Randomized Controlled Trial. (February 2022) - MacKay-Lyons, Marilyn; Gubitz, Gordon; Phillips, Stephen; Giacomantonio, Nicholas; Firth, Wanda; Thompson, Kara; Theriault, Chris; Wightman, Howard; Slipp, Sharon; Marsters, David; Eskes, Gail; Peacock, Fiona; et al.
Background: Non-disabling stroke (NDS) and transient ischemic attack (TIA) herald the possibility of future, more debilitating vascular events. Evidence is conflicting about potency of exercise and education in reducing risk factors for second stroke. Methods: Three-site, single-blinded, randomized controlled trial with 184 participants <3 months of NDS or TIA (mean age, 65 years; 66% male) randomized to usual care (UC) or UC + 12-week program of exercise and education (PREVENT). Primary (resting systolic blood pressure) and secondary outcomes (diastolic blood pressure [DBPrest], high-density lipoprotein cholesterol [HDL-C], low-density lipoprotein cholesterol [LDL-C], total cholesterol [TC], TC/HDL, triglycerides, fasting glucose, and body mass index) were assessed at baseline, post-intervention, and 6- and 12-month follow-up. Peak oxygen consumption (VO2 peak) was measured at baseline, post-intervention, 12-month assessments. Results: Significant between-group differences at post-intervention favored PREVENT group over UC: DBPrest (mean difference [MD]: −3.2 mmHg, 95% confidence interval [CI]: −6.3, −.2, P = .04) and LDL-C (MD: −.31 mmol/L, 95% CI: −.42, −.20, P = .02). Trends of improvement in PREVENT group were noted in several variables between baseline and 6-month follow-up but not sustained at 12-month follow-up. Of note, VO2 peak did not change over time in either group. Conclusion: Impact of PREVENT on vascular risk factor reduction was more modest than anticipated, possibly because several outcome variables approximated normative values at baseline and training intensity may have been sub-optimal. Further investigation is warranted to determine when exercise and education programs are viable adjuncts to pharmaceutical management for reduction of risk factors for second stroke. Clinical Trial Registration-URL: http://www.clinicaltrials.gov . Unique identifier: #NCT00885456